2012
DOI: 10.1097/jto.0b013e318265b2b5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Systematic EGFR and KRAS Mutation Evaluation on Progression-Free Survival and Overall Survival in Patients with Advanced Non–Small-Cell Lung Cancer Treated by Erlotinib in a French Prospective Cohort (ERMETIC Project—Part 2)

Abstract: EGFR and KRAS status independently impacts outcomes in advanced non-small-cell lung cancer patients treated with EGFR-TKI. However, EGFR status impacts both PFS and OS whereas KRAS only impacts OS. These findings support the nationwide use of EGFR status for patient selection before EGFR-TKI therapy. The role of KRAS mutations remains to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 26 publications
1
53
1
Order By: Relevance
“…In a landmark trial, erlotinib improved OS and quality of life when compared with the best supportive care, with a median OS benefit of 2 months relative to the placebo arm [6]. The rates of response to erlotinib were higher in some patient subgroups, including patients of Asian origin, females, neversmokers and patients with adenocarcinoma [6][7][8]. However, never-smoker status was the only clinical factor associated with improved OS in multivariable analysis.…”
mentioning
confidence: 99%
“…In a landmark trial, erlotinib improved OS and quality of life when compared with the best supportive care, with a median OS benefit of 2 months relative to the placebo arm [6]. The rates of response to erlotinib were higher in some patient subgroups, including patients of Asian origin, females, neversmokers and patients with adenocarcinoma [6][7][8]. However, never-smoker status was the only clinical factor associated with improved OS in multivariable analysis.…”
mentioning
confidence: 99%
“…In the meantime, based on eight studies (Felip et al, 2008;Schneider et al, 2008;Marchetti et al, 2009;O'Byrne et al, 2011;Sequist et al, 2011;Cadranel et al, 2012;Metro et al, 2012;Milella et al, 2012), the pooled HR for PFS was 1.33 (95%CI: 1.05-1.69, P=0.019 heterogeneity test P=0.10, I 2 =61.9%), shown in Figure 3B. The result suggested that patients with K-ras mutation had a shorter PFS than did wild-type K-ras patients.…”
Section: Predictive and Prognostic Value Of K-ras Mutationmentioning
confidence: 84%
“…Furthermore, EGFR-TKIs were more sensitive than anti-EGFR MoAbs to K-ras gene status. Eleven studies (Endoh et al, 2006;Ichihara et al, 2007;Felip et al, 2008;Schneider et al, 2008;Marchetti et al, 2009;O'Byrne et al, 2011;Sequist et al, 2011;Cadranel et al, 2012;Ludovini et al, 2012;Milella et al, 2012;Johnson et al, 2013) showed the correlation between OS and the K-ras status. Available HRs from the 11 studies were combined to get the pooled HR, shown in Figure 3A.…”
Section: Predictive and Prognostic Value Of K-ras Mutationmentioning
confidence: 99%
“…Sensitizing mutations and rearrangements in the EGFR and ALK genes, respectively, are responsible for the constitutively activated kinase, and render tumors exquisitely sensitive to TKIs. In the case of EGFR and ALK inhibitors, response rates and progression-free survival are dramatically improved compared with standard chemotherapy (6). Although TKIs are initially very effective in the majority of patients whose tumors harbor the genetic alteration, acquired resistance invariably occurs.…”
mentioning
confidence: 99%